Virtual Preaching: The New Evangelization in the New Normal - Aboy, Eugene Dominic V. (2023)
The events following the Second Vatican Council have affirmed the advantages of using social communication as a means for evangelization. The Church formally recognized, although not without its dangers, that media can serve as a modern-day “Areopagus” in which the preaching of the Gospel can be amplified. Furthermore, prompted by the needs of the time, the Roman Pontiffs beginning from Paul VI up to the present have called for a “New Evangelization” that would respond to the challenges of secularization by proclaiming the Good News through new and creative means. The unprecedented worldwide disaster brought about by the COVID-19 pandemic has only cemented the use of social communications in the life and liturgy of the Church more permanently. However, this moment of tragedy can be regarded as an opportunity for grace and transformation so that the Gospel can find new life in virtual seeds. Virtual preaching, which employs social communications as its primary tool, is thus an authentic and effective way of New Evangelization in the New Normal.
Keywords: Digitalisierung; Evangelisation; Social Media